TOG‘AY MUROD ASARLARINING BADIIY TIL XUSUSIYATLARI - Allayorov, T.R. (SCIENCE and SOCIETY, 2024)
The article reflects on the artistic-aesthetic, emotional-expressive, linguapoetic features of the linguistic units used in the works of Togay Murad, and the writer’s skill in choosing these units.